The Road to the Dayton Accords A Study of American Statecraft - Chollet, D.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2005)
The intricate diplomacy that led to the peace agreement in Bosnia, known as the Dayton Accords, is here revealed in unprecedented detail. Based on thousands of still-classified government documents and dozens of interviews with key participants, this is a comprehensive story of high-level diplomacy, told from the inside.
Keywords: Russia—Politics and government; Europe—Politics and government; Europe—History.; International relations; European Union; History, Modern; Russian and Post-Soviet Politics; European Politics; European History; International Relations; European Union Politics; Modern History